Representation of Climate Change in the Documentary Film Ano Bulan Balong (Semiotic Analysis of Roland Barthes) - Sufriatni, Sufriatni; SF, Aka Kurnia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Climate change is a condition characterized by changes in world climate patterns which result in erratic weather phenomena. Climate change occurs due to changes in climate variables, such as air temperature and rainfall, which occur continuously. In this research, film is the subject, film is a mass communication tool that is packaged with characters, plot and messages in it, provides information to the audience through the storyline that is conveyed and has a strong influence on issues that are developing in society, the unit of analysis of this research contains "Semiotic Analysis of Roland Barthes' Representation of Climate Change in the Documentary Film Ano Bulan Balong". The aim of this research is to determine the representation of climate change in the film Ano Bulan Balong based on Roland Barthes' stereotypes. This research uses Roland Barthes' semiotic theory, where the researcher looks for the meaning of Denotation, Connotation and Myth in several scenes in the film Ano Bulan Balong. . The results of research on the documentary film Ano Bulan Balong can be linked to environmental issues, namely climate change. Researchers group and categorize messages to convey meaning in the film Ano Bulan Balong, including; environmental message, Through semiotic analysis, Roland Barthes in this film shows that the problem currently being faced by Sumbawa is unrest triggered by environmental problems which are a factor in climate change, forest lands full of trees are starting to disappear, replaced by corn plants. Critical trees resulting from deforestation will cause extreme natural disasters.